Clinical efficacy and quality of life under micronutrients in combination with methotrexate therapy in chronic plaque of psoriatic patients - Hadis Yousefzadeh; Farahzad Jabbari Azad; Mahnaz Banihashemi; Maryam Rastin; Mahmoud Mahmoudi (Wolters Kluwer Medknow Publications, 2017)
Background/objectives: Psoriasis is a common dermatologic disorder, with fluctuating response to treatments. We aimed to investigate the efficacy of methotrexate (MTX) plus micronutrient supplement (MM) compare to MTX only on Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI) in psoriasis patients in a double-blinded clinical trial study. Materials and methods: A total number of 30 psoriasis patients who had lesions up to 20 percent of body skin involvement were divided randomly into two groups. Group A were treated by oral methotrexate and group B were received the MTX plus one tablet of micronutrient supplement daily for 12 weeks. Clinical response (scaling, erythema, involvement and thickness of patient's lesion), PASI score and DLQI index were recorded baseline and after 12 weeks. PASI-50, PASI-75, and PASI-90 evaluated as indicators of clinical improvements. Results: PASI 50/75/90 response rates were 100%, 73.3%, 40% in group B and they were 66.6%, 40%, 20% in group A respectively. Both treatments were effective and caused significant improvements in PASI score and DLQI (P < 0.05). Group B showed a noticeable and more rapid reduction of PASI score, scaling and involvement of lesions compared to group A (P = 0.04; P = 0.01; P = 0.03, respectively). The decline of DLQI in group B (6.80 ± 2.33) was higher than that in group A (5.40 ± 2.84). Conclusion: Daily usage of supplements along with methotrexate is safe and concomitant with the significant reduction of PASI score and improvement of DLQI compared to the usage of MTX alone.